(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Injuries resulting in flexor tendon lacerations in the upper limb are common. The flexor tendons in the hand are anatomically divided into 5 zones, each requiring different surgical approaches for tendon repair. Zone 2 injuries, in particular, pose challenges in repair techniques due to higher rates of tendon adhesion complications. Achieving secure tendon repair in Zone 2 to facilitate early active mobilization and minimize adhesion complications presents a treatment challenge. Objective: The aim is to evaluate and compare the outcomes of surgical repair for Zone 2 flexor tendon injuries in the hand, as well as the re-rupture complication rates, between the two-strand core suture technique (Group A) combined with early passive motion exercises and the four-strand core suture technique (Group B) combined with early active motion exercises. Materials and Methods: A retrospective descriptive study was conducted on 58 patients (comprising 88 fingers) with Zone 2 flexor tendon injuries who underwent primary tendon repair at the Hospital for Traumatology and Orthopedics in Ho Chi Minh City from January 2021 to June 2023. Group A consisted of 28 patients (45 fingers) with two-strand core sutures, while Group B consisted of 30 patients (43 fingers) with four-strand core sutures. Treatment outcomes were assessed based on grip strength, total active range of motion (TAM) of the fingers, surgical duration, and re-rupture rates. Results: Group B (four-strand core suture) demonstrated superior restoration of finger motion compared to Group A (two-strand core suture) with a significant difference (P = 0.038). There was no significant difference in grip strength between the two groups (P = 0.16). The re-rupture rate was 2.3% in Group B compared to 11,1% in Group A. Conclusion: Four-strand core suture repair for Zone 2 flexor tendon injuries in the hand facilitates early active mobilization, resulting in significantly improved joint motion recovery compared to the two-strand technique. Additionally, the re-rupture rate is lower with the four-strand technique.